Increased Eps15 homology domain 1 and RAB11FIP3 expression regulate breast cancer progression via promoting epithelial growth factor receptor recycling. Issue 2 (February 2017) - Tong, Dandan; Liang, Ya-Nan; Stepanova, AA; Liu, Yu; Li, Xiaobo; Wang, Letian; Zhang, Fengmin; Vasilyeva, NV
Recent research indicates that the C-terminal Eps15 homology domain 1 is associated with epithelial growth factor receptor–mediated endocytosis recycling in non-small-cell lung cancer. The aim of this study was to determine the clinical significance of Eps15 homology domain 1 gene expression in relation to phosphorylation of epithelial growth factor receptor expression in patients with breast cancer. Primary breast cancer samples from 306 patients were analyzed for Eps15 homology domain 1, RAB11FIP3, and phosphorylation of epithelial growth factor receptor expression via immunohistochemistry. The clinical significance was assessed via a multivariate Cox regression analysis, Kaplan–Meier curves, and the log-rank test. Eps15 homology domain 1 and phosphorylation of epithelial growth factor receptor were upregulated in 60.46% (185/306) and 53.92% (165/306) of tumor tissues, respectively, as assessed by immunohistochemistry. The statistical correlation analysis indicated that Eps15 homology domain 1 overexpression was positively correlated with the increases in phosphorylation of epithelial growth factor receptor ( r = 0.242, p < 0.001) and RAB11FIP3 ( r = 0.165, p = 0.005) expression. The multivariate Cox proportional hazard model analysis demonstrated that the expression of Eps15 homology domain 1 alone is a significant prognostic marker of breast cancer for the overall survival in the total, chemotherapy, and human epidermal growth factor receptor 2 (−) groups. However, the use of combined expression of Eps15 homology domain 1 and phosphorylation of epithelial growth factor receptor markers is more effective for the disease-free survival in the overall population, chemotherapy, and human epidermal growth factor receptor 2 (−) groups. Moreover, the combined markers are also significant prognostic markers of breast cancer in the human epidermal growth factor receptor 2 (+), estrogen receptor (+), and estrogen receptor (−) groups. Eps15 homology domain 1 has a tumor suppressor function, and the combined marker of Eps15 homology domain 1/phosphorylation of epithelial growth factor receptor expression was identified as a better prognostic marker in breast cancer diagnosis. Furthermore, RAB11FIP3 combines with Eps15 homology domain 1 to promote the endocytosis recycling of phosphorylation of epithelial growth factor receptor.